Hybrid revascularization procedures for multivessel disease: 2021. Issue 2 (15th February 2021) - Butman, Samuel M.
Key Points: There have only been small or pilot trials of hybrid coronary revascularization. To date, short‐term benefits, if any, are at best minimal. Hybrid coronary revascularization has not caught on for a variety of reasons. It may be considered as an option on a case‐by‐case basis.